The Analysis of Financial Management and Utilization of Village Funds In Bangunjiwo, Bantul Regency - Sastia, Sindi; Fathah, Rigel Nurul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This study aims to analyze the application of Minister of Home Affairs Regulation Number 20 of 2018 on the financial management of village funds and the suitability of Village Minister Regulation Number 13 of 2020 on the utilization of village funds in Bangunjiwo Village for the 2021 Fiscal Year. This research is a type of qualitative research with a descriptive approach. Data collection techniques used in this study were interviews, and documentation with triangulation of sources and triangulation of techniques as a test of the validity of the data that had been obtained. This study uses data analysis techniques in the field Model Miles and Huberman. The results of this study indicate that the financial management of village funds in Bangunjiwo Village in the 2021 TA as a whole at all stages is in accordance with the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. It's just that at the planning stage there was a discrepancy in article 32 paragraph 3. Meanwhile, the use of village funds in Bangunjiwo Village was in accordance with Village Minister Regulation Number 13 of 2020 concerning Priority for Use of Village Funds for 2021 Fiscal Year. Bangunjiwo Village has implemented village fund priorities according to applicable regulations regulated according to village authority with program activities for the national economic recovery, national priority programs, and new adaptation activity programs that have been prioritized for achieving the Village SDGs.